Antimicrobial activity of human α‐defensin 6 analogs: insights into the physico‐chemical reasons behind weak bactericidal activity of HD6 in vitro. (24th September 2015) - Mathew, Basil; Nagaraj, Ramakrishnan
<x xml:space="preserve">Abstract</x> Human α‐defensin 6 (HD6), unlike other mammalian defensins, does not exhibit bactericidal activity, particularly against aerobic bacteria. Monomeric HD6 has a tertiary structure similar to other α‐defensins in the crystalline state. However, the physico‐chemical reasons behind the lack of antibacterial activity of HD6 are yet to be established unequivocally. In this study, we have investigated the antimicrobial activity of HD6 analogs. A linear analog of HD6, in which the distribution of arginine residues was similar to active α‐defensins, shows broad‐spectrum antimicrobial activity, indicating that atypical distribution of arginine residues contributes to the inactivity of HD6. Peptides spanning the N‐terminal cationic segment were active against a wide range of organisms. Antimicrobial potency of these shorter analogs was further enhanced when myristic acid was conjugated at the N‐terminus. Cytoplasmic localization of the analogs without fatty acylation was observed to be necessary for bacterial killing, while they exhibited fungicidal activity by permeabilizing Candida albicans membranes. Myristoylated analogs and the linear full‐length arginine analog exhibited activity by permeabilizing bacterial and fungal membranes. Our study provides insights into the lack of bactericidal activity of HD6 against aerobic bacteria. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd.